A delicate absurdity: Teaching and thinking in times of crisis. (Revista de Ensino em Artes, Moda e Design, 2026)
Editorial of the Dossier: A delicate absurdity: Teaching, Humor, Creation and Complex Thought with/in Gianni Rodari and Edgar Morin" with a preamble on the theme, the thinkers discussed and summaries of the published contributions.
Keywords: Gianni Rodari; Edgar Morin; arts education; complexity theory; fantastic binomial